Successful breeding attempt of a pair of Philippine tarsier (Tarsius syrichta) in a conservation center in Bilar, Bohol, Philippines and recommendations for tarsier husbandry - Řeháková, Milada (Zoo biology, 2019)
The Philippine tarsier (Tarsius syrichta) belongs to the least known nocturnal primates. Tarsiers and remaining biodiversity of the Philippines are under tremendous threats from increasing human expansion, with habitat loss and illegal pet trade being the main reasons for tarsier population decline. In addition, even though the attempts were made by western and local facilities, tarsiers have not survived well in captivity. In this paper, I present an example of successful breeding of the Philippine tarsier in captive conditions but in natural climate. As the most important elements of success, I see a large amount of space provided to tarsiers, the climate similar to their natural habitat and the food resembling their natural diet. Our pair of tarsiers were joined during the mating period and held separately outside the mating period, which corresponds with their behavior in the wild and may have played a crucial role in breeding success. Eliminating stress to animals is also important. The study can provide valuable guidelines for other facilities keeping tarsiers in the Philippines and help to improve tarsiers' welfare and in the future help to establish a viable captive population of the Philippine tarsier that will serve as a backup population and also will decrease demand on tarsiers captured from the wild.
Keywords: chov zvířat; bydlení zvířat; rozmnožování; Diet; dieta; Reproduction; zvířata; Housing, Animal; Animal Husbandry; Tarsiidae; Animals